Evaluating standards-based assessment rubrics in a postgraduate public health subject - Kite, James; Phongsavan, Philayrath (Assessment and evaluation in higher education, 2017)
Standards-based assessment rubrics are recognised as an important tool for ensuring clear criteria in higher education. Most of the available evidence on rubrics comes from studies with face-to-face undergraduate students. Our study evaluated the introduction of rubrics into a postgraduate subject that included both online and face-to-face students. We conducted formative evaluation with former students to develop the rubrics, as well as surveying current students for process and impact evaluation, supplemented with a focus group. Process results showed that the rubrics were used widely and were generally considered to be of at least some use. Clarity of the rubrics was the main issue affecting perceived usefulness, particularly for the assessment tasks that had undergone comparatively less formative evaluation. Impact evaluation showed mixed results, with students that reported always using rubrics having higher marks on average compared to students who did not always use the rubrics. However, an expected improvement in marks across the whole student cohort compared to previous years did not eventuate, although this could be explained by a number of factors independent of the rubrics. Our results provide some evidence for the use of rubrics in postgraduate and online settings but highlight the need for rigorous formative evaluation.